Microplastic Pollution in Waters and its Impact on Health and Environment in Indonesia: A Review - Basri K, Sarinah; K, Basri; Syaputra, Eko Maulana; Handayani, Sri (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2021)
Introduction: Microplastics have become a pollution problem that has received worldwide attention. Microplastics in the water impact the environment and health, especially in Indonesia, which is the second-largest plastic waste contributor in the world. This literature study aims to determine the distribution of microplastics pollution in waters and its impact on health and the environment in Indonesia.Methods: The literature search on papers from 2010-2021 through Google Scholar, Pubmed, ScienceDirect, and ProQuest, with the keywords of ‘Microplastics’, ‘Indonesia’, ‘aquatic’, ‘environment’ found 477 articles. Then, after the exclusion of duplicate articles, and other inclusion criteria, the final review was done on 42 articles. PRISMA guidelines were used for reviewing the procedure.Results: Most microplastic research was conducted in Java Island, which is dominated by rivers and beaches. Based on the source, microplastics came from domestic waste, tourism, and fishing activities. The most common forms found were black and blue fibers from fishing lines, nets, and clothing fibers of various sizes. The type of polymer identified is polyethylene plastic. Microplastics impacted tourist destinations, marine ecosystems through the food chain, and also humans who consume seafood.Conclusion: Microplastics are found in the Indonesian marine environment. Humans can consume seafood contaminated with microplastics, which will have an impact on health. Therefore, a health risk assessment should be done to provide information for taking environmental management efforts.